A Real-World Retrospective Analysis of Secondary Prevention Patients Treated with Inclisiran over 27 Months - Carl Deaney; Meredith Donaldson; Agne Meskauskiene (Clinical Medicine Insights: Cardiology)
ASCVD is a global concern as it has become central to significant morbidity and mortality. LDL-C is the most important modifiable risk factor in developing ASCVD. Therefore, lowering LDL-C levels is paramount to tackling ASCVD; the lower the LDL-C, the better. Finding the right combination of medications patients are willing to adhere to is necessary for optimal lipid lowering. Inclisiran is a novel LDL-C lowering LLT that has demonstrated around 50% reduction in LDL-C with a low side effect profile. As long-term data is limited for Inclisiran, this retrospective analysis aims to observe whether Inclisiran’s benefits are sustained as monotherapy and in combination with other LLTs. After 27 months, the clinic found sustained drops in LDL-C of 59% with good adherence. Only 4% of patients reported experiencing side effects, with 1 individual needing to discontinue the medication due to these effects. Our data indicates that incorporating Inclisiran into a patient’s LDL-C treatment plan can provide long-term LDL-C reduction, thereby helping to decrease cardiovascular events.